Magnetooptic coupling coefficients for one- and two-magnon Raman scattering in the rutile-structure antiferromagnets FeF2, MnF2, CoF2 and NiF2: Оптика и магнитооптика - Lockwood, D.J.; Cottam, M.G. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
Inelastic light scattering intensities of magnetic excitations are governed by the magnetooptic coupling coefficients, which have been evaluated, for example, for the ferrimagnet Y3Fe5O12 (YIG) and the metamagnets FeCl2 and FeBr2. However, by far the most detailed studies to date have been performed on the classic rutilestructure antiferromagnets, and we summarize here the results obtained from the many experimental and theoretical investigations in these compounds for both one-magnon and two-magnon excitations. A comparison of the magnitudes of the various coupling coefficients for MnF2, FeF2, CoF2, and NiF2 reveals a surprising similarity in many coefficients. In one-magnon Raman scattering, the in-phase linear magnetooptic coefficient dominates and the main differences between MnF2, FeF2, and NiF2 lie in the relative significance of the in-phase quadratic magnetooptic coefficient. Thus the quadratic coefficients are now seen to be of particular importance in determining the strength of the one-magnon scattering in a variety of magnetic insulators. In two-magnon Raman scattering, one magnetooptic coefficient dominates for all of these antiferromagnets. However, each of the other six coefficients are remarkably similar in magnitude, in general, and not negligible in most cases, indicating some universality in the way light interacts with the pairs of magnons of opposite and equal wave vector in rutile structure antiferromagnets.